The failure of the German labor market - Horst Siebert (Kiel Institute for World Economics (IfW), 2003)
The paper analyzes why Germany experiences the high and sticky unemployment. It looks at wage policy and proposes a new approach to measure productivity growth when unemployment increases. It studies the position of trade unions and the institutional set-up of the labor market. It looks at the role of the reservation wage for the lower segment of the labor market and discusses the impact of contributions to social security on the demand for labor. – – Der Beitrag analysiert, warum die Arbeitslosigkeit in Deutschland so hoch ist. Er diskutiert die Rolle der Lohnpolitik und schlägt eine neue Methode vor, das Produktivitätswachstum bei zunehmender Arbeitslosigkeit zu messen. Die Machtposition der Gewerkschaften und das institutionelle Regelwerk für Arbeit werden erörtert. Ferner wird die Bedeutung des ?Reservation Wage" für das untere Segment des Arbeitsmarktes und der Beiträge zur Sozialversicherung für die Nachfrage nach Arbeitskräften behandelt.
Keywords: J0; I3; 330; Institutional arrangement; Reservation wage; Social security; Unemployment; Arbeitslosigkeit; Lohnpolitik; Arbeitsproduktivität; Lohnstruktur; Gewerkschaftlicher Organisationsgrad; Tarifpolitik; Anspruchslohn; Arbeitsmarktflexibilisierung; Deutschland